Challenges and Insights in Aggregatibacter aphrophilus endocarditis: a review of literature - Zacarías Mendoza, Nathalie Victoria (2023)
Infective endocarditis is a serious disease associated with high mortality despite recent advances in diagnosis and treatment. Aggregatibacter aphrophilus is a fastidious Gram-negative member of the HACEK organisms (Haemophilus spp., Aggregatibacter actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae). A. aphrophilus is associated with dental infections but has also been implicated in cases of infective endocarditis. We highlight the importance of a high index of suspicion in symptomatic patients with an initial negative blood culture, particularly in high-risk groups such as patients with congenital valve disease and prosthetic valve. The knowledge of this rare entity may lead to early diagnosis and appropriate management. We review the main characteristics of Aggregatibacter aphrophilus endocarditis reported in the medical literature.